Balancing Safety, Comfort, and Fall Risk: An Intervention to Limit Opioid and Benzodiazepine Prescriptions for Geriatric Patients. (2nd September 2022) - Bloomer, Ainsley; Wally, Meghan; Bailey, Gisele; Roomian, Tamar; Karunakar, Madhav; Hsu, Joseph R; Seymour, Rachel; Beuhler, Michael; Bosse, Michael; Gibbs, Michael; Griggs, Christopher; Jarrett, Steven; et al.
Introduction: This study reports on the impact of a clinical decision support tool embedded in the electronic medical record and characterizes the demographics, prescribing patterns, and risk factors associated with opioid and benzodiazepine misuse in the older adult population. Significance: This study reports on prescribing patterns for patients ≥65 years-old who presented to Emergency Departments (ED) or Urgent Care (UC) facilities across a large healthcare system following a fall (n = 34, 334 encounters; n = 25, 469 patients). This system implemented a clinical decision support intervention which provides an alert when the patient has an evidence-based risk factor for prescription drug misuse; prescribers can continue, amend or cancel the prescription. Results: Of older adults presenting with a fall, 31.4% (N = 7986) received an opioid or benzodiazepine prescription. Women and younger patients (65-74) had a higher likelihood of receiving a prescription ( P < .0001). 11% had ≥1 risk factor. Women were more likely to receive an early refill ( P = .0002) and younger (65-74) men were more likely to have a past positive toxicology ( P < .0001). A prescription was initiated in 8, 591 encounters, and 946 (9.0%) triggered an alert. In 58 cases, the alert resulted in a prescription modification, and in 80 the prescription was canceled. Conclusions: Documented risk for opioid misuse in the elderly was 10% among patients presenting to the ED/UC after a fall. The dangers associated with opioid/benzodiazepine use increase with age as does fall risk. Awareness of risk factors is an important first step; more work is needed to address potentially hazardous prescriptions in this population.